2010
DOI: 10.1200/jco.2009.24.6397
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxes in Advance Care Planning: The Complex Relationship of Oncology Patients, Their Physicians, and Advance Medical Directives

Abstract: A B S T R A C T PurposeMany seriously ill patients with cancer do not discuss prognosis or advance directives (ADs), which may lead to inappropriate and/or unwanted aggressive care at the end of life. Ten years ago, patients with cancer said they would not like to discuss ADs with their oncologist but would be willing to discuss them with an admitting physician. We assessed whether this point of view still held. Patients and MethodsSemi-structured interviews were conducted with 75 consecutively admitted patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
150
3
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(169 citation statements)
references
References 25 publications
10
150
3
6
Order By: Relevance
“…21,22 These low LW rates are not unexpected, especially in the United States, given the paucity of advance care planning in America, 1 whether among the healthy, the elderly, the hospitalized, 23 those undergoing major surgical procedures, 24 or those with cancer. 25,26 In contrast to the low frequency of LWs, we found a much higher percentage of patients with HCPs. Our contemporary analysis replicates prior studies 1,14,15,18,27 in both oncologic and medical-surgical critically ill populations, which shows that the presence of LWs has no impact on ICU care patterns, EOL management, and outcomes.…”
Section: Discussioncontrasting
confidence: 48%
“…21,22 These low LW rates are not unexpected, especially in the United States, given the paucity of advance care planning in America, 1 whether among the healthy, the elderly, the hospitalized, 23 those undergoing major surgical procedures, 24 or those with cancer. 25,26 In contrast to the low frequency of LWs, we found a much higher percentage of patients with HCPs. Our contemporary analysis replicates prior studies 1,14,15,18,27 in both oncologic and medical-surgical critically ill populations, which shows that the presence of LWs has no impact on ICU care patterns, EOL management, and outcomes.…”
Section: Discussioncontrasting
confidence: 48%
“…In the report of the Virginia patients, only 7% reported having an AD discussion with their oncologist; moreover, only 23% said they would like to discuss AD with their oncologist (5). When Snyder and colleagues surveyed primary care physicians regarding their understanding of and experience with advance care planning (2), they found that only 43% reported having those discussions with the appropriate patients; 44% felt that the discussions took too much time, and most felt that the appropriate time to have the conversation was in the estimated last 6 months of life (6). Th e inclusion of other specialists and mid-level providers may help overcome the time constraints that some physicians face.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of patients admitted to a hematology-oncology inpatient service in Virginia provided information about their preferences and attitudes toward AD and which physicians they preferred to host the discussion (6). Of the 75 patients enrolled in the study, nearly all (95%) thought that discussing an AD was very or somewhat important, but only 41% had an existing AD.…”
mentioning
confidence: 99%
“…Preceding surveys showed that 20-40% of cancer patients report on having a completed AD (living will and/or durable power of attorney for health care) and that this rate has remained constant over many years [3,4,5,6]. It seems to be even lower than 20% in different European countries independent of the detailed legal situation [7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation challenged this conclusion and showed that cancer patients would prefer their oncologist if he made ‘the first step' toward initiating an AD discussion [4]. These surveys only included hospitalized cancer patients.…”
Section: Introductionmentioning
confidence: 99%